Human Aortic Endothelial Cell Labeling with Positive Contrast Gadolinium Oxide Nanoparticles for Cellular Magnetic Resonance Imaging at 7 Tesla - Yasir Loai; Nurus Sakib; Rafal Janik; Warren D. Foltz; HL Cheng (Molecular Imaging)
Positive T 1 contrast using gadolinium (Gd) contrast agents can potentially improve detection of labeled cells on magnetic resonance imaging (MRI). Recently, gadolinium oxide (Gd 2 O 3 ) nanoparticles have shown promise as a sensitive T 1 agent for cell labeling at clinical field strengths compared to conventional Gd chelates. The objective of this study was to investigate Gado CELL Track, a commercially available Gd 2 O 3 nanoparticle, for cell labeling and MRI at 7 T. Relaxivity measurements yielded r 1 = 4.7 s −1 mM −1 and r 2 / r 1 = 6.2. Human aortic endothelial cells were labeled with Gd 2 O 3 at various concentrations and underwent MRI from 1 to 7 days postlabeling. The magnetic resonance relaxation times T 1 and T 2 of labeled cell pellets were measured. Cellular contrast agent uptake was quantified by inductively coupled plasma–atomic emission spectroscopy, which showed very high uptake compared to conventional Gd compounds. MRI demonstrated significant positive T 1 contrast and stable labeling on cells. Enhancement was optimal at low Gd concentrations, attained in the 0.02 to 0.1 mM incubation concentration range (corresponding cell uptake was 7.26 to 34.1 pg Gd/cell). Cell viability and proliferation were unaffected at the concentrations tested and up to at least 3 days postlabeling. Gd 2 O 3 is a promising sensitive and stable positive contrast agent for cellular MRI at 7 T.